Robust and persistent SARS-CoV-2 infection in the human intestinal brush border expressing cells - Sunhee Lee; Gun Young Yoon; Jinjong Myoung; Seong-Jun Kim; Dae-Gyun Ahn (Emerging Microbes and Infections)
Studies on patients with the coronavirus disease-2019 (COVID-19) have implicated that the gastrointestinal (GI) tract is a major site of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We established a human GI tract cell line model highly permissive to SARS-CoV-2. These cells, C2BBe1 intestinal cells with a brush border having high levels of transmembrane serine protease 2 (TMPRSS2), showed robust viral propagation, and could be persistently infected with SARS-CoV-2, supporting the clinical observations of persistent GI infection in COVID-19 patients. Ectopic expression of viral receptors revealed that the levels of angiotensin-converting enzyme 2 (ACE2) expression confer permissiveness to SARS-CoV-2 infection, and TMPRSS2 greatly facilitates ACE2-mediated SARS-CoV-2 dissemination. Interestingly, ACE2 but not TMPRSS2 expression was significantly promoted by enterocytic differentiation, suggesting that the state of enterocytic differentiation may serve as a determining factor for viral propagation. Thus, our study sheds light on the pathogenesis of SARS-CoV-2 in the GI tract.